1959
DOI: 10.1139/m59-025
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses of Some Insects to Some Bacterial Antigens

Abstract: Pseudomonas aeruginosa (Schroeter) Migula antigen remained in the blood of larvae of the wax moth, Galleria mellonella (L.), during the resistant period of the insect. Bacterial antigen present in the immune blood produces agglutinating titers in rabbits about 10 times as great a s those produced by a n approximately equal volume of standard P. aeruginosa vaccine. Attempts to demonstrate the mechanism that enhances the antigen showed that the active portion was contained in the serum, that the action occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

1967
1967
2006
2006

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(24 citation statements)
references
References 16 publications
2
21
0
1
Order By: Relevance
“…But it has been recognised for many years that 'immunisation' with killed bacteria (e.g. with Pseudomonas aeruginosa -Stephens, 1959-Stephens, , 1962 or prior infection with living bacteria (e.g. with Enterobacter cloacae- Boman et al, 1972Boman et al, , 1974 can induce in insects a temporary state of markedly enhanced resistance to subsequent infection, either to the same bacterium or a different one.…”
Section: Introductionmentioning
confidence: 99%
“…But it has been recognised for many years that 'immunisation' with killed bacteria (e.g. with Pseudomonas aeruginosa -Stephens, 1959-Stephens, , 1962 or prior infection with living bacteria (e.g. with Enterobacter cloacae- Boman et al, 1972Boman et al, , 1974 can induce in insects a temporary state of markedly enhanced resistance to subsequent infection, either to the same bacterium or a different one.…”
Section: Introductionmentioning
confidence: 99%
“…L'existence de réac tions humorales chez les Insectes n'a jamais été prouvée pour les parasites métazoaires ; mais Briggs (1958) et Stephens (1959) semblent avoir démontré son existence vis-à-vis des bactéries. L'observation de destruction de filaires dans l'haemocoele, sans faire intervenir de mécanisme cellulaire, ne peut à elle seule prouver la mise en jeu, dans ce cas, de mécanismes humoraux ; on peut penser en effet, comme l'écrit Salt (1963) que la destruction du parasite n'est qu'un effet retardé de substances nocives qui seraient présentes uniquement dans le tube digestif.…”
Section: Relationsunclassified
“…aeruginosa seemed to be relatively heat stabile as compared with the cultures used by other workers (28,30,46), Three sets of 15 larvae each of W strain, and three sets of 15 larvae each of the N strain of Galleria were treated with 4 jul/larva of bacterin.…”
Section: Smentioning
confidence: 89%
“…Stephens (46) showed that Pseudomonas aeruginosa bacterins would protect Galleria mellonella larvae from challenge with viable cells, that the antigen (immunogen) remained in the hemolymph throughout the re fractory period (unlike the situation in vertebrates where the antigen needs to be processed), and that the antigen was somehow altered during immunity in the insect so that it has an increased antigenicity for rabbits.…”
Section: Immunity In Invertebrates Other Than Arthropodsmentioning
confidence: 99%
See 1 more Smart Citation